Peran Komunikasi Orang Tua dalam Meningkatkan Keterampilan Sosial Anak Usia Dini di Desa Naru - Karolina Laurentia Bule Tawa; Konstantinus Dua Dhiu; Efrida Ita; Gde Putu Arya Oka (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The urgency of this research is to provide a real description of how parents in rural areas perceive and understand their role in shaping children's social skills through communication. The objective of this study is to determine the role of parental communication in forming and improving early childhood social skills. The research method used is qualitative with a descriptive approach. Data were collected through observation, interviews, and documentation, and then analyzed using the Miles, Huberman, and Saldana model, which includes data reduction, data display, and conclusion drawing. The research subjects consisted of parents, teachers, and early childhood children in Naru Village, Bajawa District, Ngada Regency. The results showed that parents in Naru Village are aware of the importance of communication in shaping children's social attitudes. Parental communication plays a significant role, although its intensity varies due to work constraints.